Death and dying: what do you know about!!! - Sanders, Pete; Myers, Steve; Lacey, Mike (Brookfield, Conn. : Copper Beech Books, 1998)
Explores the feelings and issues that may arise after the death of a loved one and the importance of confronting such issues.
Includes index.
73603
Keywords: Children and death -- Juvenile literature; Death -- Psychological aspects -- Juvenile literature; Bereavement in children -- Juvenile literature; Bereavement -- Psychological aspects; Grief in children -- Juvenile literature; Grief -- Juvenile literature; Death; Grief